Pengetahuan Ibu Rumah Tangga dengan Perilaku Hidup Bersih dan Sehat di Desa Baluase Kecamatan Dolo Selatan Kabupaten Sigi - Susianawati, Desak Eka; Arni HR, Fitri; Fitriani; Ambodale, Saiful; Kantohe, Imelda; Purwiningsih, Sri; Taurisa, Almaida; Kasim, Atia Kurnia (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
This activity aims to open up homemakers' knowledge regarding Clean and Healthy Living Behavior (PHBS). It also seeks to change their behavior by implementing PHBS in everyday life, such as using clean water, washing hands with clean water and soap, using healthy restrooms, and not smoking in the house. Community service was conducted in Baluase Village, South Dolo District, Sigi Regency, with 42 homemakers. The method used is an analytical method with a cross-sectional approach using proportional random sampling. The results of community service show that the knowledge and insight of homemakers in Baluase Village, South Dolo District, increased by 40% regarding their understanding or mastery of PHBS material, which we adopted as the primary material in service activities.